2003
DOI: 10.1039/b304710e
|View full text |Cite
|
Sign up to set email alerts
|

Thiram: degradation, applications and analytical methods

Abstract: In this review a brief introduction to thiram (tetramethylthiuram disulfide; TMTD) pesticide has been given along with other applications. All the important methods available are systematically arranged and are listed under various techniques. Some of these methods have been applied for the determination of thiram in commercial formulations, synthetic mixtures in grains, vegetables and fruits. A comparison of different methods is the salient feature of this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 38 publications
0
87
0
Order By: Relevance
“…Appropriate dilutions are required when the method is applied to real samples as the maximum residue limits for dithiocarbamates (expressed as CS2), which are allowed by the European Union to be 2 -7 mg kg -1 . 5 The method has limits of detection of 10, 8.0 and 5.0 ng mL -1 for maneb, nabam and thiram, respectively. The method is better in terms of sensitivity and sample throughput than the methods reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Appropriate dilutions are required when the method is applied to real samples as the maximum residue limits for dithiocarbamates (expressed as CS2), which are allowed by the European Union to be 2 -7 mg kg -1 . 5 The method has limits of detection of 10, 8.0 and 5.0 ng mL -1 for maneb, nabam and thiram, respectively. The method is better in terms of sensitivity and sample throughput than the methods reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive reviews on thiram pesticide in environmental and pharmaceutical samples have also been reported. 23,24 These methods are sensitive and accurate; however, many of these involve expensive methods, and toxic solvents; they are slow and require the development of extremely complex gradients for separation. Table 1 gives a comparison among several methods for the determination of thiram, nabam and maneb in terms of the sample matrix and the sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formulations of thiram are available as dust, flowable or wettable powder, water dispensable granules and water suspensions (Kidd and James, 1991). Thiram is used as a fungicide to protect harvested crops and prevent crop damage in the field, and as a seed protectant to prevent various fungal diseases (Han et al, 2003;Sharma et al, 2003;Bradley et al, 2007). It is also used in rubber industry as an accelerator and a vulcanization agent (Ceresera et al, 2001;Grosicka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among many methods available for the detection of thiram and related substances, gas chromatography, high performance liquid chromatography, thin layer densitometry, Fourier transform infrared spectroscopy, capillary electrophoresis and voltammetry have been successful for a variety of sample matrices (Procopio et al, 1988;Sharma et al, 2003;Weliwegamage, 2005 and2008). Special reagents have been used in many of these techniques to improve selectivity and/or sensitivity.…”
Section: Introductionmentioning
confidence: 99%